2008
DOI: 10.2478/v10051-008-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Management Control Systems - Strategy Interaction on Performance Management: A Case Study

Abstract: We study the interaction between management control systems and strategy and its impact on organisational performance considering the way in which multiple aspects of control systems and dimensions of context combine in a variety of ways to enhance performance. Our purpose is to investigate the relationship among management control systems, strategy and organisational performance in a particular company. The contribution of this study is that it upgrades the existing theory in that it does not only establish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…In a case study by Peljhan and Tekavćić (2008), it was confirmed that a combination of performance-driven behaviour and regular use of management control systems lead to improved results. Jubilee insurance believes that a careful blend of control systems and strategy have the capability of improving performance as suggested by Peljhan and Tekavćić (2008). One notable philosophy of the company is that failure can be costly if not checked and avoided.…”
Section: Performance Challenges and Policy Implications In The Kenyanmentioning
confidence: 89%
“…In a case study by Peljhan and Tekavćić (2008), it was confirmed that a combination of performance-driven behaviour and regular use of management control systems lead to improved results. Jubilee insurance believes that a careful blend of control systems and strategy have the capability of improving performance as suggested by Peljhan and Tekavćić (2008). One notable philosophy of the company is that failure can be costly if not checked and avoided.…”
Section: Performance Challenges and Policy Implications In The Kenyanmentioning
confidence: 89%
“…Some studies have, however, found greater extent of use. Peljhan and Tekavcic (2008) on a scale of 1 to 7 found a mean of 4.618 whilst Widener (2007) with a similar scale reported a mean value of 4.74. Casebased research summarily provide support for use of belief control systems in Indexed African Journals Online: www.ajol.info enhancing a positive effect on a managers' values to lead to increasing focus on a firms strategic direction, (McCartney& Rouse, 2004;Marginson, 2002).…”
Section: Extent Of Practice Of Belief Control Systemsmentioning
confidence: 97%
“…In contrast, Khan (1999) in a retrospective longitudinal study reported that belief control systems only appeared after the first seven years of a firm's existence, suggesting absence of the same at formative stages of the company. Prior studies which have found belief control systems to be critical in orgnizations seeking to maintain coherence in complex and uncertain environments (Peljhan & Tekavcic, 2008;Bartlett & Ghoshal 1993;Simons 1995b). In such situations, belief control systems have been used to overcome inertia Bruining et al, 2004).…”
Section: Extent Of Practice Of Belief Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Business strategies (cost leadership, differentiation strategy) can be significantly attained by incorporating all levels of control in an MCS [83]. Furthermore, the MCS is a facilitating system in the implementation of business strategies, that is employed to support workers involved in the management process to accomplish organizational goals [84].…”
Section: Mcs As a Package (Mcsp)mentioning
confidence: 99%